Dynamical heterogeneity of NaNO2 confined within porous glasses - Dvornikov, V.; Korotkov, L.; Naberezhnov, A.; Fokin, A.; Korotkova, T. (Oficyna Wydawnicza Politechniki Wrocławskiej, 2008)
Frequency dependences of imaginary part of the dielectric response ε'(f) of SiO2–NaNO2 nanocomposite, prepared by embedding of sodium nitrite into porous glasses with 7 nm average pore diameter, have been studied within a temperature range of 360–520 K. It has been found that the spectrum S(ω) = ε'(f)/f contains the component ~1/fα, where α is a coefficient indicating the dynamical heterogeneity of dipoles. Peculiarities of the temperature dependence of α are discussed.
Optica Applicata, Vol. 38, 2008, nr 1, s. 25-29
Keywords: optyka; nanostructured ferroelectrics; porous glasses; dielectric responce